Quantum Mechanics - Bracken, Paul (IntechOpen, 2020)
Quantum mechanics touches all areas of physics, chemistry, life sciences, and engineering. It has emerged as a tool for researching and developing new technology that has had a deep impact on modern life. An essential ingredient of quantum mechanics is the role of the observer and the duality between particle and wave properties of matter at very small scales. This book covers such topics as complex space forms of quantum mechanics, entropy in quantum mechanics, and equations of relativistic quantum mechanics as well as applications of quantum mechanics to more complicated situations. Written by international experts, the book illustrates the wide scope, influence, and applicability of quantum mechanics.